Understanding the role of probation: observing the effectiveness of probation as an alternative to incarceration in Larimer County, Colorado - Hilgendorf, John, author; Opsal, Tara, advisor; Hogan, Michael, committee member; Moore, Scott, committee member (Colorado State University. Libraries, 2017)
Probation is the largest component of the United States criminal justice system, and its population has significantly grown over the past few decades. However, probation is an understudied area of criminal justice research, even though so many individuals fall under the supervision of probation. The purpose of this thesis is to observe if probation is serving its intended purpose as an alternative to incarceration, or if revocations from probation result in future jail sentences. The study uses data from Larimer County Criminal Justice Services in Larimer County, Colorado to understand how successful different probation sentences, with varying levels of surveillance and monitoring, serve as diversions from traditional forms of incarceration. The findings show that probation sentences with higher levels of supervision commonly result in probation revocations, and as a result, jail sentences due to revocations. Therefore, the findings suggest supervised probation sentences do not successfully divert offenders from incarceration, but rather contribute to jail populations in Larimer County.